4 Accelerating transition to practice: innovative and collaborative multi-centre simulation training for specialist nurse-organ donation (SN-OD) uk. (17th November 2016) - Fores, M; Gosling, N; Miller, C; Woodier, N; Miles, G; Snelgrove, H
Abstract : Background: This course was developed for NHS Blood and Transplant Authority (NHS-BT) as part of a national modular induction programme for SN-OD's, in collaboration with Trent Simulation and Clinical Skills Centre (TSCSC) Nottingham, St George's Advanced Patient Simulation Centre (GAPS) London, and the Education and Service Development Team for NHS BT. The aim being to consolidate learning and accelerate SN-OD transition into practice. Enhancement of the traditional clinical educational model with simulation based medical education with deliberate practice should be a high priority for medical education. 1 Method: A three day simulation course was designed guided by specific outcomes from the SN-OD induction programme .The course was multicentre (GAPS & TSCSC). Faculty consisted of the simulation centre teams, NHS BT Education Team and Clinical Leads for Organ Donation. Two cohorts have completed the programme. A post course on-line questionnaire collected both quantitative (Likert scoring system) and qualitative data and was completed by 33/36 (n = 33) and faculty (n = 15) over the 2 cohorts. Results: This pilot was considered a success with positive evaluations from faculty and candidates. Of the 33 respondents, 32 agreed that the simulation training increased knowledge related to the organ donation process and that they were better equipped with the necessary skills to undertake the SN-OD role (97%). The majority of participants felt that simulation was something that must be included in the SN-OD induction course (82%). The qualitative data was largely positive, also providing insight into candidate views relating to peer observation and feedback. Regarding time taken to achieve competency on the rota – data compares favourably for both cohorts, 6–8 months compared to traditional SN-OD induction 5–14 months. Conclusion: The deceased donation simulation training was highly valued by the new SN-ODs, and evaluation of its impact suggests evidence for its continued inclusion in future induction courses Acknowledgements: I would like to thank the NHS BT Education and Service Development Team, Trent Simulation and Clinical Skills Centre and St Georges Advanced Patient Simulation Centre in production of this paper. Reference: WC McGaghie, SB Issenberg, ER Cohen, JH Barsuk, and DB Wayne. Does Simulation-Based Medical Education With Deliberate Practice Yield Better Results Than Traditional Clinical Education? A Meta-Analytic Comparative Review of the Evidence. Acad Med 2011;86 (6):706–711.